2017
DOI: 10.18632/oncotarget.16774
|View full text |Cite
|
Sign up to set email alerts
|

Significance of inflammation-based indices in the prognosis of patients with non-metastatic colorectal cancer

Abstract: Previous studies demonstrated that several inflammation-based hematological indices are closely related to various malignancies, including colorectal cancer (CRC). In this study, the prognostic value of inflammation-based markers, including a combination index termed coNLR-PDW, comprising the preoperative neutrophil-to-lymphocyte ratio (NLR) and the platelet distribution width (PDW), was evaluated in 206 patients with non-metastatic CRC treated with surgery at a single medical center. The association of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
1
33
2
Order By: Relevance
“…Our most interesting finding is the demonstration of prognostic significance of higher values of PDW on admission in internal medicine wards. Higher PDW levels have recently been reported to be associated with increased morbidity and mortality in numerous clinical investigations that focused on patients with critical illness [11,13], and with specific acute and chronic disorders [10,[14][15][16][17][18][19][20][21][22][23]. We observed that PDW values above the cut-off of 16.7% at admission, as well as above the normal range, were associated with an increased risk of mechanical ventilation and death during the current hospitalization, and shortened survival following discharge.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our most interesting finding is the demonstration of prognostic significance of higher values of PDW on admission in internal medicine wards. Higher PDW levels have recently been reported to be associated with increased morbidity and mortality in numerous clinical investigations that focused on patients with critical illness [11,13], and with specific acute and chronic disorders [10,[14][15][16][17][18][19][20][21][22][23]. We observed that PDW values above the cut-off of 16.7% at admission, as well as above the normal range, were associated with an increased risk of mechanical ventilation and death during the current hospitalization, and shortened survival following discharge.…”
Section: Discussionmentioning
confidence: 52%
“…Increased PDW values have been reported in patients with diabetes mellitus [5], cancer [6,7], and cardiocerebrovascular and respiratory disorders [8][9][10][11][12]. Moreover, higher PDW levels have recently been reported to be associated with increased morbidity and mortality among patients with critical illness [11,13], coronary artery disease [14][15][16][17], cancer [18][19][20][21], pulmonary embolism [10,22], and chronic obstructive pulmonary disease [23]. Most previous studies on the clinical significance of PDW involved patients with specific disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is an essential component of the tumour microenvironment, and the changes in inflammatory cells might influence tumour progression, such as neoplastic cell proliferation, migration, invasion, collapse of anti-tumour immunity, metastasis, and so forth [5,6]. Accumulating evidence shows that the peripheral neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) have been widely proposed as prognostic factors for many malignancies such as gastric cancer [7], nasopharyngeal carcinoma [8], liver cancer [9], and especially colorectal cancer [10]. Moreover, it is likely that the tumour microenvironment as well as systemic inflammatory response might be changed because of surgery [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, there is a growing interest of the host's inflammatory response against the tumor. Several studies have proposed NLR, PLR, and TPC as indicators of inflammatory conditions, and these indicators were described as both prognostic and predictive biomarkers in some cancers (Monreal et al, 1998;Forget et al, 2013;Lee et al, 2013;Pedrazzani et al, 2017;Song et al, 2017;Zhang et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%